﻿Beneficial effects of vitamin D in the management of untreated hyperlipidemia in diabetic patients in Erbil, Iraq - Mohammed Khoshnaw; Kawa Dizaye (Pensoft Publishers, 2022)
Hyperlipidemia is highly prevalent among type 2 diabetes mellitus (T2DM) patients. As hyperlipidemia plays a major part in atherosclerosis development and progression, this occurrence is linked to a significantly raised risk of cardiovascular disease. This study aims to assess the effects of vitamin D supplementation on lipid parameters in T2DM patients with untreated hyperlipidemia. Thirty-five T2DM patients with hyperlipidemia and vitamin D deficiency were supplemented with vitamin D for three months. Serum 25-hydroxyvitamin D (25[OH]D), calcium, lipid parameters, atherogenic indices, glucose, and HbA1c were recorded before and after the intervention. After supplementation, there was a statistically significant reduction in VLDL-C and triglycerides. Triglycerides showed a significant negative correlation with 25(OH)D. Atherogenic indices and HDL-C also improved significantly. Vitamin D supplementation had beneficial effects on the lipid profile of T2DM patients with untreated hyperlipidemia and vitamin D deficiency. Thus, vitamin D could be a valuable adjuvant therapy for these patients.